LBA15Overall survival with first-line durvalumab plus platinum-etoposide in patients with extensive-stage (ES)-SCLC in CASPIAN: Subgroup findings from Asia. (24th November 2019) - Nishio, M; Ji, J H; Hotta, K; Chiu, C-H; Lee, J-S; Azuma, K; Kim, S-W; Wu, S-Y; Dvorkin, M; Trukhin, D; Havel, L; Hochmair, M J; et al.
Abstract: Background: CASPIAN is an open-label, phase III study of first-line durvalumab (D), ± tremelimumab (T), plus etoposide and either cisplatin or carboplatin (EP) for the treatment of pts with ES-SCLC. In a planned interim analysis (IA), D+EP significantly improved OS vs EP alone (primary endpoint; HR 0.73 [95% CI 0.59–0.91]; p = 0.0047). We report prespecified exploratory results at this IA for pts recruited in Asia. Methods: Treatment-naïve pts with ES-SCLC were randomised (1:1:1) to D 1500 mg + EP q3w; D 1500 mg + T 75 mg + EP q3w; or EP q3w. Pts in the immunotherapy arms received up to 4 cycles of EP followed by maintenance D q4w until progression. Pts in the EP arm received up to 6 cycles of EP and PCI (investigator's discretion). Investigator's choice of cisplatin or carboplatin (stratification factor) was permitted. Data cutoff: 11 March 2019. Results: Of the 537 pts in the D+EP and EP arms, 76 (14.2%) were randomised in Japan, South Korea, Taiwan or China (Asia subgroup). Some differences were observed in baseline characteristics between the Asia subgroup and overall population. Median OS for D+EP vs EP in the Asia subgroup was 14.8 vs 11.9 months (HR 0.87 [95%CI 0.45, 1.64]). More pts in the Asia subgroup vs the overall population received subsequent anticancer therapy (63.2 vs 43.2%; balanced between arms). Incidence of any cause SAEs was higher in the Asia subgroup vs the overall population regardless of treatment; AEs leading to discontinuation was less. In the Asia subgroup, for D+EP vs EP, the incidence of any cause grade 3/4 AEs was 62.9 vs 76.9%; respective incidences of SAEs and AEs leading to discontinuation were: 42.9 vs 48.7% and 5.7 vs 7.7%. The D+T+EP arm continues to final analysis. Conclusions: In the CASPIAN overall population, D+EP improved OS vs EP; results were consistent in this prespecified subgroup of patients recruited in Asia. The safety profile of D+EP in the Asia subgroup was also consistent with the overall population, with no new signals identified. Clinical trial identification: NCT03043872 (Release date, 6 February 2017) EudraCT number: 2016-001203-23. Editorial acknowledgement: Rebecca Douglas, PhD of Cirrus Communications (Macclesfield, UK), an Ashfield company, funded by AstraZeneca. Legal entity responsible for the study: AstraZeneca PLC. Funding: AstraZeneca. Disclosure: M. Nishio: Honoraria (self): Ono Pharmaceutical; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Pfizer; Honoraria (self): Chugai Pharmaceutical; Honoraria (self): Eli Lilly; Honoraria (self): Taiho Pharmaceutical; Honoraria (self): AstraZeneca; Honoraria (self): MSD; Honoraria (self): Novartis; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Sankyo Healthcare; Honoraria (self): Merck Serono; Research grant/Funding (self): Ono Pharmaceutical; Research grant/Funding (self): Bristol-Myers Squibb; Research grant/Funding (self): Pfizer; Research grant/Funding (self): Chugai Pharmaceutical; Research grant/Funding (self): Eli Lilly; Research grant/Funding (self): Taiho Pharmaceutical; Research grant/Funding (self): AstraZeneca; Research grant/Funding (self): MSD; Research grant/Funding (self): Novartis; Research grant/Funding (self): Astellas, All outside the submitted work. K. Hotta: Research grant / Funding (self), Grants and personal fees: AstraZeneca / Lilly / Bristol-Myers Squibb; Travel / Accommodation / Expenses, Personal fees: MSD / Ono / Nipponkayaku / Taiho / Boehringer Ingelheim / Chugai. C-H. Chiu: Honoraria (self): AstraZeneca; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Chugai Pharmaceutical; Honoraria (self): Eli Lilly; Honoraria (self): Merck Sharp & Dohme; Honoraria (self): Novartis; Honoraria (self): Ono Pharmaceutical; Honoraria (self): Pfizer; Honoraria (self): Roche; Honoraria (self): Takeda. K. Azuma: Honoraria (self), Lecture fees: Ono Pharmaceutical Co Ltd / Bristol-Myers Squibb / AstraZeneca KK / Chugai Pharmaceutical. M. Özgüroğlu: Advisory / Consultancy: Janssen / Sanofi / Astellas; Honoraria (self): Novartis / Roche / Janssen / Sanofi / Astellas; Travel / Accommodation / Expenses: Bristol-Myers Squibb / Janssen. J. Bar: Research grant / Funding (institution): MSD / AstraZeneca / Roche / BMS / Takeda / AbbVie / Pfizer; Travel / Accommodation / Expenses, Personal fees: AstraZeneca / MSD / Boehringer Ingelheim / Roche / BMS / Takeda / AbbVie / Pfizer / VBL. Y. Chen: Research grant / Funding (self): AstraZeneca / Ipsen / Roche / Bristol-Myers Squibb; Travel / Accommodation / Expenses, Personal fees: AstraZeneca / Genentech / Bristol-Myers Squibb / Merck / Novartis / Takeda / Eli Lilly / Guardant Health / Pfizer / Array Biopharma. J.W. Goldman: Research grant / Funding (self): AstraZeneca/MedImmune / Eli Lilly / Genentech / Bristol-Myers Squibb / Array BioPharma; Research grant / Funding (self): Celgene / AbbVie; Advisory / Consultancy: AstraZeneca / Genentech; Advisory / Consultancy: Lilly; Speaker Bureau / Expert testimony, Speakers' Bureau: Merck. N. Byrne: Full / Part-time employment, Contractor: AstraZeneca; Shareholder / Stockholder / Stock options: AstraZeneca. P.J. Laud: Full/Part-time employment: AstraZeneca, Contractor. N. Shire: Full / Part-time employment: AstraZeneca; Shareholder / Stockholder / Stock options: AstraZeneca. L. Paz-Ares: Honoraria (self): Roche/Genentech / Lilly / Pfizer/ Boehringer Ingelheim / BMS / MSD / AstraZeneca / Merck Serono; Honoraria (self): PharmaMar / Novartis / Celgene / Sysmex / Amgen / Incyte; Travel / Accommodation / Expenses: Roche / AstraZeneca / AstraZeneca Spain / MSD / BMS / Lilly / Pfizer; Leadership role, Myself: Genomica; Leadership role, An immediate family member: European Medicines Agency; Spouse / Financial dependant, Other relationship: Novartis / Ipsen / Pfizer / Servier / Sanofi / Roche / Amgen / Merck.